Chitosan-Silica (CS/Sc) Composites as Promising Adsorbents for Fe(III) Removal in Water Purification - Yulida Amri; Fakhira Khairana; Ida Ratna Nila; Rahmatul Fajri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Fe(III) contaminated water has become a serious environmental concern, creating a need for effective and affordable adsorbents. This study evaluates the performance of chitosan silica (CS/Sc) composites for Fe(III) removal. CS/Sc composites were synthesized via a sol-gel route by varying the volume ratio of 1% chitosan to 5% silica. The ratio significantly influenced surface morphology. The 4:3 composition showed silica dominance with an inhomogeneous surface, while the 4:4 composition exhibited a more porous and homogeneous structure. The 4:5 composition yielded the most homogeneous and porous surface, exhibiting increased Si and N signals, which indicate a stronger interaction between chitosan and silica. Fe(III) adsorption tests were conducted at pH 2. Both adsorption capacity (q) and adsorption efficiency (η) increased with increasing silica proportion. The CS/Sc 4:3 composite showed an adsorption capacity q of 0.391 mg g⁻¹ and an adsorption efficiency η of 5.211%. The 4:4 composite reached q of 2.701 mg g⁻¹ and η of 36.012%. The highest performance was obtained with the 4:5 composite, yielding a q of 3.266 mg g⁻¹ and an η of 43.542%. These results demonstrate that the CS/Sc composite with a 4:5 ratio is the most promising formulation for Fe(III) removal and water purification applications. The novelty of this work lies in the targeted application of CS/Sc composites for Fe(III) adsorption, which has been rarely reported, and in providing insight into how compositional variation affects structure and adsorption performance